Chlormethine Gel is Efficient and Safe in Mycosis Fungoides Skin Lesions - Marios Koumourtzis; Kyriaki Lampadaki; Maria Dalamaga; Evangelia Papadavid (Acta Dermato-Venereologica, 2022)
Chlormethine is a bifunctional cytotoxic alkylating agent that binds to DNA, resulting in cell death (apoptosis). Chlormethine (also known as mechlorethamine) gel (CL gel) was approved in the European Union in 2017 and was first used in 2019. The aim of the study is to examine evidence regarding the efficacy and safety of chlormethine gel in everyday clinical experience from a cutaneous lymphoma centre. Twenty-three patients with stage IA–IIB mycosis fungoides received chlormethine gel between September 2020 and May 2021. All patients started by applying the gel daily and were monitored every month. At 1, 3, 6 and 9 months, 0%, 43.47%, 56.52% and 65.22% of patients, respectively, achieved an overall response. Five out of 23 patients (21.73%) achieved near complete response at a mean time of 6 months. Chlormethine gel was given as monotherapy in 12 patients (52.17%), and in addition to systemic treatments (methotrexate and peginterferon alpha-2a) in 11 patients (47.82%). Adverse events (AE) were recorded in 43.47% of patients, but only 3 discontinued treatment, due to dermatitis. Scale down of the treatment to application 3-times per week led to better patient compliance. This study shows that chlormethine gel is effective and safe in patients with mycosis fungoides with different types of skin lesions.